The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1080/15216549800201772
|View full text |Cite
|
Sign up to set email alerts
|

The effects of lifelong ubiquinone Q10 supplementation on the Q9 and Q10 tissue concentrations and life span of male rats and mice

Abstract: SUMMARYThe effect of lifelong oral supplementation with ubiquinone Qlo (10 mg/kg/day) was examined in Sprague-Dawley rats and C57/B17 mice. There were no significant differences in survival or life-span found in either rats or mice. Histopathologic examination of different rat tissues showed no differences between the groups. In Qlo supplemented rats, plasma and liver Qio levels were 2.6 to 8.4 times higher at all age points than in control rats. Interestingly, in supplemented rats the Q9 levels also were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
31
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 18 publications
7
31
1
Order By: Relevance
“…This is very important because any putative benefit of dietary supplementation with CoQ 10 might be maintained through the whole life (Quiles et al, 2004). According to our studies (Gómez-Díaz et al, 2003;Bello et al, 2005; this work) and those from others (Sugiyama et al, 1995;Forsmark-Andrée et al, 1997;Matthews et al, 1998;Lönnrot et al, 1998;Kwong et al, 2002), plasma and liver show a better adaptation pattern to dietary CoQ 10 than organs like brain or heart. In accordance, significant decrease in CoQ 9 /CoQ 10 ratio was also found in liver samples obtained from the same animals (Bello et al, 2005).…”
Section: Discussionsupporting
confidence: 52%
“…This is very important because any putative benefit of dietary supplementation with CoQ 10 might be maintained through the whole life (Quiles et al, 2004). According to our studies (Gómez-Díaz et al, 2003;Bello et al, 2005; this work) and those from others (Sugiyama et al, 1995;Forsmark-Andrée et al, 1997;Matthews et al, 1998;Lönnrot et al, 1998;Kwong et al, 2002), plasma and liver show a better adaptation pattern to dietary CoQ 10 than organs like brain or heart. In accordance, significant decrease in CoQ 9 /CoQ 10 ratio was also found in liver samples obtained from the same animals (Bello et al, 2005).…”
Section: Discussionsupporting
confidence: 52%
“…8). Two previous studies on mice and rats in other laboratories, in which CoQ 10 was administered at dosages lower than the highest dosage used by us, also reported no effect on life span (Lonnrot et al, 1998;Lee et al, 2004). Results of studies in other species are, however, quite contradictory and species-specific.…”
Section: Coq Intake Mitochondrial Function and Life Span In Micecontrasting
confidence: 53%
“…Several reports show that the penetrance of coenzyme Q into the rodent brain is very marginal [23,26]. In contrast, one study showed that feeding 12 month-old rats 200 mg/ kg/day of coenzyme Q for 2 months increases brain mitochondrial content of this cofactor by over 50% [28].…”
Section: Discussionmentioning
confidence: 96%